The School Story - Clements, Andrew 1949-; Selznick, Brian (New York : Simon & Schuster Books for Young Readers, 2001)
After twelve-year-old Natalie writes a wonderful novel, her friend Zoe helps her devise a scheme to get it accepted at the publishing house where Natalie's mother works as an editor.
Keywords: Authorship -- Fiction; Publishers and publishing -- Fiction